If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-16m-16=-16
We move all terms to the left:
-16m-16-(-16)=0
We add all the numbers together, and all the variables
-16m=0
m=0/-16
m=0
| 7x+5=65+5x | | 6x-9x=4-2x-2 | | 24n+3=24n | | 1/2x+2=1/4x-1 | | 9y-13=4y+7 | | -2-x=2x+7 | | 66(3x)=899 | | 5(4x/5-×)=10(×/10-9/2) | | 1/5(25-10b)+4=1/3 | | 8(x+1)=-2(x+19) | | 1/3(x+1)-x=1/3 | | 6(z-2+4)=10 | | 10x-3x+5=33 | | 135+2x=0+7x | | 24=2y-12 | | 36a+2(a+6)=28 | | 20=3/2x | | 6(z-2+4=10 | | 0.1x=0.15x+2 | | -x-2(2x+1)=3-x+(-10) | | x+3x-6=16+10 | | 5=1/2x-15 | | -3-3x=3-x | | U=2x-2,x | | 24=-3r=-9 | | -x/3=32/3 | | 0=-4.9t^2+25t+75 | | 3z/2-2z/3=-10 | | 6(m-2)=12+6 | | 20w-20=20w-25 | | X-2(2x+1)=3-x+(-10) | | 6(m-2)=12+7 |